The turtle of Michigan a novel - Nye, Naomi Shihab 1952- (Greenwillow Books, 2022)
Eight-year-old Aref is excited to reunite with his father in Ann Arbor, Michigan, where he will start a new school, and while Aref misses his grandfather, his Sidi, he knows that his home in Oman will always be waiting for him
Keywords: Emigration and immigration / Juvenile fiction; Moving, Household / Juvenile fiction; Families / Juvenile fiction; Schools / Juvenile fiction; Michigan / Juvenile fiction; Oman / Juvenile fiction; Emigration and immigration / Fiction; Moving, Household / Fiction; Family life / Fiction; School / Fiction; Michigan / Fiction; Oman / Fiction; Émigration et immigration / Romans, nouvelles, etc. pour la jeunesse; Déménagement / Romans, nouvelles, etc. pour la jeunesse; Familles / Romans, nouvelles, etc. pour la jeunesse; Écoles / Romans, nouvelles, etc. pour la jeunesse; Michigan / Romans, nouvelles, etc. pour la jeunesse; JUVENILE FICTION / Social Themes / Emigration & Immigration; JUVENILE FICTION / Social Themes / Self-Esteem & Self-Reliance; JUVENILE FICTION / Social Themes / Emotions & Feelings; JUVENILE FICTION / Diversity & Multicultural; Emigration and immigration; Moving, Household; Families; Schools; Michigan / https://id.oclc.org/worldcat/entity/E39PBJjHhdXqPcpRBtfF98RMyd; Oman / https://id.oclc.org/worldcat/entity/E39PBJtMkkM3XYkYtjG6c8khpP; Immigration and emigration / Juvenile fiction; Moving / Juvenile fiction; Family / Juvenile fiction; Immigration and emigration / Fiction; Moving / Fiction; School stories; Children's stories; Fiction; Juvenile works; Domestic fiction; Novels; Romans; Kinderbuch